Vaping leads tobacco consumption among university students in Arab countries: a study of behavioral and psychosocial factors associated with smoking - Sallam, Malik; Alnazly, Eman Khamis; Sajwani, Adil; Al-Mahzoum, Kholoud; Alkhalaf, Yousef; Aldaihani, Aisha; Aldousari, Abdulrahman; Alhajeri, Mohammad; Almutairi, Meshari; Alnajdi, Shekha; Alkhozam, Mohammad; Alsubaiei, Abdulaziz Muneer; et al. (Frontiers in Public Health, 2025)
BackgroundE-cigarettes use “vaping” is a growing public health concern. The Arabic-validated Vaping Attitude and Perceptions Scale (VAPeS) instrument assesses vaping determinants across five constructs: Social Influence, Perceived Harms, Vaping Pleasure, Behavioral Influences, and Economic and Self-Efficacy. We aimed to examine the prevalence of cigarette, e-cigarette, and narghile use among Arab university students and to identify the associations between demographic/VAPeS-related variables and the smoking attitudes among vapers.MethodsA cross-sectional survey was distributed online among university students across Arab countries during January–April 2025. Prevalence estimates were calculated using one-sample proportions with Wilson Score confidence intervals. The modified VAPeS scale comprising four constructs after confirmatory factor analysis (Social Influence, Perceived Benefits, Behavioral Influence - Risk, and Behavioral Influence - Situational Triggers) was used to assess tobacco use attitudes. The primary outcome was the Endorsement of Tobacco Use Attitude Score (ETUAS). Multivariate analyses using multinomial logistic and linear regressions were conducted to examine factors associated with tobacco use attitudes.ResultsAmong 1,338 university students surveyed, the majority were from Kuwait (21.0%), Egypt (18.5%), Kingdom of Saudi Arabia (KSA, 17.8%), Jordan (16.7%), and the United Arab Emirates (UAE, 10.0%). Vaping was the most prevalent form of tobacco use (21.2%), surpassing narghile (12.9%) and cigarette smoking (10.8%). Multivariate analyses revealed that male students were more likely to engage in all three tobacco use forms. Male sex was associated with higher prevalence of vaping (adjusted odds ratio (AOR) = 6.97; p < 0.001), with higher odds among UAE students (AOR = 2.31; p = 0.013), and lower odds among those studying in Egypt, Jordan, and KSA. Among current smokers, the mean ETUAS indicated a moderate level of agreement with attitudinal statements endorsing tobacco use (3.25 ± 0.92). In linear regression among vapers, male sex (B = −0.325; p = 0.003), Social Influence (B = 0.300; p < 0.001), and Behavioral Influence - Situational Trigger (B = 0.205; p = 0.002) were significantly associated with favorable attitudes toward tobacco use.ConclusionThis multinational study found vaping to be the leading form of tobacco use among Arab university students. Favorable attitudes toward tobacco use were associated with male sex, social influence, and the situational triggers. Interventions should target social normalization, strengthen regulations, and apply tools like VAPeS to understand youth vaping risks.